Posttraumatic Stress Symptoms and the Quality of Maternal-Child Interactions in Mothers of Preterm Infants. Issue 9 (29th December 2022) - Elansary, Mei; Zuckerman, Barry; Patts, Gregory; Antonio, Jocelyn; Mayes, Linda C.; Silverstein, Michael
Abstract : This article has supplementary material on the web site: www.jdbp.org . ABSTRACT: Objective: The purpose of this study was to examine associations between maternal trauma exposure, posttraumatic stress symptoms, and directly observed maternal-child interactions among a diverse cohort of mother-preterm infant dyads at 12-month corrected age. Methods: We conducted a retrospective cohort study. Maternal trauma exposure and posttraumatic stress symptoms were measured using the Modified Posttraumatic Stress Disorder Symptom Scale at baseline and 6 and 12 months. The primary outcome was directly observed maternal-child interactions at 12-month corrected age using the Coding Interactive Behavior Manual. We used linear regression models to estimate the associations between trauma exposure, posttraumatic stress symptoms (and symptom clusters), and observer-rated maternal-child interactions. Results: Among the 236 participants, 89 (37.7%) self-reported as Black and 98 (41.5%) as Latina; mean gestational age of the infants was 31.6 weeks (SD 2.6). Mothers with posttraumatic stress symptoms demonstrated greater maternal sensitivity (β = 0.32; 95% confidence interval [CI], 0.06–0.58; standardized effect size = 0.39) and greater dyadic reciprocity (β = 0.39; 95% CI, 0.04–0.73; standardized effect size = 0.36) compared with those not exposed to trauma; however, we did not observe significant differences between trauma-exposed but asymptomatic women and those not exposed to trauma. Across symptom clusters, differences in maternal sensitivity and dyadic reciprocity were most pronounced for mothers with avoidance and re-experiencing symptoms, but not hyperarousal symptoms. Conclusion: Maternal posttraumatic stress symptoms seem to be associated with the quality of maternal-child interactions at age 1 year among a cohort of urban, mother-preterm infant dyads. These findings have implications for strength-based intervention development.